Characterizing outcomes in a large cohort of latinx patients with autoimmune hepatitis - Eleanor Belilos; Jessica Strzepka; Ethan Ritz; Nancy Reau; Costica Aloman (Annals of Hepatology)
Introduction and Objectives: This study aimed to characterize a large cohort of Latinx patients with autoimmune hepatitis (AIH) and analyze clinical outcomes, including biochemical remission, duration of steroid treatment, fibrosis regression, and incidence of clinical endpoints (hepatic decompensation, need for liver transplant, and death). Materials and Methods: This was a retrospective descriptive study of patients with biopsy proven AIH (2009–2019) at a single urban center. Demographics, medical comorbidities, histology, treatment course, biochemical markers, fibrosis using dynamic non-invasive testing (NIT), and clinical outcomes at three months and at one, two, and three years were analyzed. Results: 121 adult patients with biopsy-proven AIH were included: 43 Latinx (35.5%) and 78 non-Latinx (65.5%). Latinx patients were more likely to have metabolic dysfunction-associated steatotic liver disease (MASLD) (p = 0.004), and had higher Fibrosis-4 (FIB-4) (p = 0.0279) and AST-to-Platelet-Ratio-Index (APRI) (p = 0.005) at one year. Latinx patients took longer to reach biochemical remission than non-Hispanic Whites (p = 0.031) and longer to stop steroids than non-Hispanic Blacks (p = 0.016). There were no significant differences based on ethnicity in histological fibrosis stage at presentation or incidence of clinical endpoints. Conclusions: MASLD overlap is highly prevalent in Latinx AIH patients. Longer time to biochemical remission and worse NITs support that this population may have slower fibrosis regression with standard of care AIH treatment. This may indicate differing response rates due to genetic polymorphisms affecting drug metabolism and immune response among Latinx individuals and is less likely related to AIH/MASLD overlap based on the findings of this study.